Acetabular Delamination: Epidemiology, Histological Features, and Treatment. (July 2019) - Jannelli, Eugenio; Parafioriti, Antonina; Acerbi, Alberto; Ivone, Alessandro; Fioruzzi, Alberto; Fontana, Andrea
Objective: The International Cartilage Repair Society classification is the one mainly used to define chondral defects. However, this classification does not include delamination. The objective of the study is to describe the characteristics of this lesion to better explain its classification in the context of chondral lesions of the hip. Design: We performed a retrospective analysis of 613 patients who underwent hip arthroscopy. In this group, the incidence, localization, histological characteristics, and association to femoroacetabular impingement as well as to other intraarticular lesions of acetabular delamination (AD) were analyzed. Preoperative magnetic resonance imaging accuracy and the different treatment options were also evaluated. Results: In our series, the incidence of the AD was 37% (226 patients over 613). The average age of this group was significantly lower (39.3 years) than the entire group of patients. Isolated cam ( P < 0.01) and pincer morphologies ( P < 0.05) had a significant statistical association with the AD. This lesion was primarily localized at the acetabular chondrolabral junction, mainly on the anterosuperior quadrant. The intraarticular lesions more frequently associated to AD were labral lesions (94.25%, P < 0.01), ligamentum teres lesions (28.32%, P < 0.05), and femoral head chondral lesions (19.9%, P < 0.01). The histological examination of the AD was characterized by hypocellularity and structural disorder of the matrix, with fissures. Treatment remains controversial. Conclusion: AD represents an intermediate stage in chondral damage and can be classified as a "2a" grade lesion. Histological examination confirms the intermediate and progressive character of this injury.